2019
DOI: 10.1111/febs.14762
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and mechanistic studies of p38α MAP kinase phosphorylation by MKK6

Abstract: Bistability (coexistence of two stable steady states in a dynamical system) is a key mechanism of cellular decision‐making and has been observed in many biochemical reaction networks such as mitogen‐activated protein kinase (MAPK) signaling pathways. Theoretical studies have shown that bistability can arise in a single two‐site MAPK phosphorylation and dephosphorylation cycle. However, the bistable behavior mostly relies on the kinetic mechanisms and parameters of this two‐site modification. In exploring the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Kinetic data have shown that the dual-phosphorylation of p38α by MKK6 involves a partially processive mechanism in vitro, in which the monophosphorylated intermediates can either dissociate from the enzyme or proceed to the next catalytic step. Wang et al (51) and others (52) proposed that both p38α monophosphorylated forms can be produced by MKK6 catalysis with a preference for Y182, whose phosphorylation is four-fold faster than that of T180. With respect to the second catalytic step, the experimentally measured kinetic rates indicate that phosphorylation at Y182 in the first step enhances the catalytic efficiency of MKK6 phosphorylation at T180 in the second step.…”
Section: Freedom Of Interaction At the Catalytic Centrementioning
confidence: 99%
“…Kinetic data have shown that the dual-phosphorylation of p38α by MKK6 involves a partially processive mechanism in vitro, in which the monophosphorylated intermediates can either dissociate from the enzyme or proceed to the next catalytic step. Wang et al (51) and others (52) proposed that both p38α monophosphorylated forms can be produced by MKK6 catalysis with a preference for Y182, whose phosphorylation is four-fold faster than that of T180. With respect to the second catalytic step, the experimentally measured kinetic rates indicate that phosphorylation at Y182 in the first step enhances the catalytic efficiency of MKK6 phosphorylation at T180 in the second step.…”
Section: Freedom Of Interaction At the Catalytic Centrementioning
confidence: 99%
“…Wang et al . ( 61 ) and others ( 62 ) propose that both p38α monophosphorylated forms can be produced by MKK6 catalysis with a preference for Y182, whose phosphorylation is four times as fast as that of T180. With respect to the second catalytic step, the experimentally measured kinetic rates indicate that phosphorylation at Y182 in the first step enhances the catalytic efficiency of MKK6 phosphorylation at T180 in the second step.…”
Section: Discussionmentioning
confidence: 99%
“…Kinetic data have shown that the dual phosphorylation of p38a by MKK6 involves a partially processive mechanism in vitro, in which the monophosphorylated intermediates can either dissociate from the enzyme or proceed to the next catalytic step. Wang et al (61) and others (62) propose that both p38a monophosphorylated forms can be produced by MKK6 catalysis with a preference for Y182, whose phosphorylation is four times as fast as that of T180. With respect to the second catalytic step, the experimentally measured kinetic rates indicate that phosphorylation at Y182 in the first step enhances the catalytic efficiency of MKK6 phosphorylation at T180 in the second step.…”
Section: Freedom Of Interaction At the Catalytic Centermentioning
confidence: 99%
“…Our findings on the processivity of Hog1 phosphorylation may have important implications to explain dynamic properties of MAPK pathways in mammalian systems. For example, the mammalian Hog1 homolog p38 was recently shown to be phosphorylated in a semi-processive manner 47 , which may be best explained by a mixed activation model. Likewise, mammalian ERK shows context-specific differences in its ratio of single and double phosphorylated species 48 .…”
Section: Discussionmentioning
confidence: 99%